The Influence of Side-Slip Velocity on Subsurface Displacement - Imam Setiaji Ronoatmojo; Muhammad Burhannudinnur; Yarra Sutadiwiria; Dewi Syavitri (Testing Center for Oil and Gas LEMIGAS, 2024)
This research aimed to determine the influence of side-slip velocity on subsurface displacement during seismic data acquisition. Anisotropy constants were used to determine the depth migration process before stack, which showed inadequate results after data validation. Therefore, the forward modeling of a medium, which comprised anisotropy constants of normal and offset raytracing was conducted to address this problem. The configuration of source to receiver were orthogonal and slant. The results showed that the migration process failed to resolve the geological structures of the position shifting. The configuration of source to receiver were orthogonal and slant. The results show the better continuity of slant and the influence of complex geological structures controls the position shifting, which could not be resolved by the migration process. It could be seen from the random distribution of the normal shift of group velocity and phase velocity, as well as the CDP – CRP shift. It produced wave azimuth rotation in a discontinuity plane, such as fault and anticline ridge. This azimuth rotation was strongly suspected to cause inaccurate anisotropy constants implementation in pre-stack depth migration process